FORMATION OF POWER RAW ORIENTATION OF THE RUSSIAN EXPORT: FROM GRAIN TO OIL - A. Rudneva (Вестник университета)
In the article genesis of commodity structure of export of Russia is considered on the basis of the retrospective analysis in the context of the developed comparative advantages of the economy. The particular emphasis is placed on traditional character of raw components of the domestic export and gradual nature of reorientation of its structure to mineral raw materials. The commodity structure of export of Russia which developed as a result of it explains sensitivity of the national economy to pricing in the world market of oil and predetermines need of search of a new paradigm of development.